2006
DOI: 10.1111/j.1469-1809.2005.00258.x
|View full text |Cite
|
Sign up to set email alerts
|

Adrenergic Receptor Polymorphisms Associated with Resting Heart Rate: The HyperGEN Study

Abstract: SummaryThe association between polymorphisms in the β1, β2 and α2B adrenergic receptor (ADR) genes (ADRB1, ADRB2 and ADRA2B) and resting heart rate was examined in white and African-American participants of the HyperGEN Study. All analyses were adjusted for age, sex, body mass index, alcohol use, smoking status and daily exercise within strata of race, hypertension status and beta-blocker use. The Ser49Gly polymorphism of the β1 ADR was associated with resting heart rate in hypertensive African-Americans and h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
1
3

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 21 publications
0
15
1
3
Order By: Relevance
“…Since increased sympathetic tone may contribute to HR elevation (3), and “tagging” genetic variation at the CYB561 locus may predict responses to pre-synaptic stimulation in humans (4), here we examined the association of sympathetic pathway gene CYB561 with HR traits, focusing on functional (rather than simply “tagging”) genetic variation. Already, it was known that genetic variation across the adrenergic pathway – GCH1 (5), TH (6), DBH (7), PNMT (8), and ADRB1 (9) – predicted control of HR; thus, we focused here on CYB561 . We found that common genetic variation in the CYB561 was confined to the 3’-UTR at A+1485G, which disrupted a micro-RNA recognition motif.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since increased sympathetic tone may contribute to HR elevation (3), and “tagging” genetic variation at the CYB561 locus may predict responses to pre-synaptic stimulation in humans (4), here we examined the association of sympathetic pathway gene CYB561 with HR traits, focusing on functional (rather than simply “tagging”) genetic variation. Already, it was known that genetic variation across the adrenergic pathway – GCH1 (5), TH (6), DBH (7), PNMT (8), and ADRB1 (9) – predicted control of HR; thus, we focused here on CYB561 . We found that common genetic variation in the CYB561 was confined to the 3’-UTR at A+1485G, which disrupted a micro-RNA recognition motif.…”
Section: Discussionmentioning
confidence: 99%
“…The role of heredity in control of HR has not been exhaustively examined, but genetic variation in the sympathetic pathway, including “tagging” (intronic) variation at the cytochrome b561 ( CYB561 ) locus reportedly influences cardiovascular responses to sympathetic activation (4). Indeed, naturally occurring genetic variation at every other point in the adrenergic pathway – GCH1 (5), TH (6), DBH (7) , PNMT (8) , and ADRB1 (9) – has already been associated with altered HR control, yet the interaction of CYB561 and HR is still unexplored.…”
Section: Introductionmentioning
confidence: 99%
“…More than 50 genes associated with heart rhythm have been identified in mice [25], and differences by sex and strain of animals have also been found [26]. In the HyperGEN Study, Wilk et al [27] found that the proportion of variance in resting heart rate explained by genetic factors was 24% in African-Americans and 27% for whites. Given this evidence for epistasis in the endophenotype of heart rate and given the number of endophenotypes that may be involved in sustained blood pressure elevation, it is little wonder that genome wide association studies of hypertension have been difficult to replicate.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have tested these variants with various CV phenotypes, including blood pressure (BP) 15 , heart rate 16 , dilated cardiomyopathy 17 and composite CV outcomes 18 . However, less is known about the relation of ADRB1 variants to the pathology and pharmacogenetics of ischemic stroke.…”
Section: Introductionmentioning
confidence: 99%